2010
DOI: 10.1038/nature09530
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and functional adaptation in surface ocean planktonic prokaryotes

Abstract: The understanding of marine microbial ecology and metabolism has been hampered by the paucity of sequenced reference genomes. To this end, we report the sequencing of 137 diverse marine isolates collected from around the world. We analysed these sequences, along with previously published marine prokaryotic genomes, in the context of marine metagenomic data, to gain insights into the ecology of the surface ocean prokaryotic picoplankton (0.1-3.0 mm size range). The results suggest that the sequenced genomes def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
264
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(282 citation statements)
references
References 44 publications
17
264
0
1
Order By: Relevance
“…Recent studies using various approaches have consistently identified statistical correlations between the ecological strategies and genome content in marine bacteria (Lauro et al, 2009;Yooseph et al, 2010;Luo et al, 2012;Luo et al, 2013). Gene functional categories involved in cell-cell interactions, such as motility, secondary metabolite synthesis and degradation, and defense mechanisms, are repeatedly found to be enriched in the genomes of marine bacteria that are associated with particles and take advantage of ephemeral patchiness of nutrients (Moran et al, 2004;Newton et al, 2010;Luo et al, 2013), while they are depleted in the genomes of marine bacteria that live as single cells in nutrient-poor bulk seawater (Giovannoni et al, 2005;Giovannoni et al, 2008).…”
Section: Sar11 Evolutionary Origin H Luomentioning
confidence: 99%
“…Recent studies using various approaches have consistently identified statistical correlations between the ecological strategies and genome content in marine bacteria (Lauro et al, 2009;Yooseph et al, 2010;Luo et al, 2012;Luo et al, 2013). Gene functional categories involved in cell-cell interactions, such as motility, secondary metabolite synthesis and degradation, and defense mechanisms, are repeatedly found to be enriched in the genomes of marine bacteria that are associated with particles and take advantage of ephemeral patchiness of nutrients (Moran et al, 2004;Newton et al, 2010;Luo et al, 2013), while they are depleted in the genomes of marine bacteria that live as single cells in nutrient-poor bulk seawater (Giovannoni et al, 2005;Giovannoni et al, 2008).…”
Section: Sar11 Evolutionary Origin H Luomentioning
confidence: 99%
“…HTCC2255. HTCC2255 is a proteorhodopsin-containing Roseobacter of the NAC11-7 clade (Newton et al, 2010;Yooseph et al, 2010) isolated by dilution-to-extinction near the coast of Oregon as part of the highthroughput culture collection (Connon and Giovannoni, 2002). HTCC2255 was also the most frequently identified taxon in both of the water samples used for validation studies, constituting 425% of Figure S4).…”
Section: Metatranscriptomic Analysis Of Montereymentioning
confidence: 99%
“…They are globally distributed (Pommier et al, 2007) in a variety of marine environments such as coastal, offshore, sediments and hydrothermal vents Pommier et al, 2007). In a recent analysis of metagenomes from the Global Ocean Sampling, Yooseph et al (2010) determined which genomes from cultured microorganisms recruited the most fragments from the metagenomes. Polaribacter sp.…”
Section: Introductionmentioning
confidence: 99%